Síntese e caracterização de materiais KNb1-XTaXO3(0≤ X ≤1) aplicados na fotodescoloração do corante remazol amarelo ouro - Souto, Ismael Dionísio (2018)
The yellow gold remazol dye (RNL) has an azo group, which is characterized by the presence of the -N = N-, chromophore of the molecule, attached to aromatic rings. Among the main processes for discoloration of this type of dye is the heterogeneous photocatalysis that uses semiconductors under radiation incidence to promote the electron / hole pair. The class of perovskite type semiconductors has proved to be efficient when acting as photocatalysts. The present work aimed to synthesize, characterize and apply perovskites containing niobium and tantalum, with the general formula KNb1-xTaxO3, with the proportion of tantalum varying from 0%, 25%, 50%, 75% and 100% in RNL discoloration. The synthesis of the materials was through the solid state (ceramic). X-ray diffraction (XRD), ultraviolet and visible (UV-Vis) absorption spectroscopy, infrared (IR) vibration spectroscopy, Raman spectroscopy, surface area analysis were performed for characterization. BET), elemental analysis by X-ray fluorescence (EDX), photoluminescence (PL) and zero charge potential (PCZ). As the proportion of tantalum increases in each material, it happens the change of the space group, leaving orthorhombic, passing through the tetragonal structure until the cubic one. All the materials presented photocatalytic activities. With the use of isopropanol as a hydroxyl sequester and with the acidification of the reaction medium, it was possible to conclude that the mechanism of the photocatalysis happens through the indirect mechanism due to the fall of the photocatalytic activity. In the final reaction medium at pH 6, the material that presented the greatest discoloration capacity was the perovskite KTaO3 containing only tantalum.